2008
DOI: 10.1002/pro.8
|View full text |Cite
|
Sign up to set email alerts
|

RosettaHoles: Rapid assessment of protein core packing for structure prediction, refinement, design, and validation

Abstract: We present a novel method called RosettaHoles for visual and quantitative assessment of underpacking in the protein core. RosettaHoles generates a set of spherical cavity balls that fill the empty volume between atoms in the protein interior. For visualization, the cavity balls are aggregated into contiguous overlapping clusters and small cavities are discarded, leaving an uncluttered representation of the unfilled regions of space in a structure. For quantitative analysis, the cavity ball data are used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
140
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 18 publications
3
140
0
Order By: Relevance
“…1, top panel) includes hydrophobic side chain atoms CH 1 , CH 2 , CH 3 as well as hydrophobic backbone atoms in loops, which are more similar to side chain hydrophobic atoms than those atoms in sheet or helix configurations. For the parameters up to the radius of hydrogen, this group of atoms displays spatial preferences consistent with more uniform packing in crystal structures and clumped arrangements in decoys, as observed previously 4 ; these hydrophobic atoms prefer a small amount of void volume immediately surrounding the atom and discourage void volume further from the atomic surface. This effect is observed for all atom types but is most pronounced for hydrophobic atoms.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…1, top panel) includes hydrophobic side chain atoms CH 1 , CH 2 , CH 3 as well as hydrophobic backbone atoms in loops, which are more similar to side chain hydrophobic atoms than those atoms in sheet or helix configurations. For the parameters up to the radius of hydrogen, this group of atoms displays spatial preferences consistent with more uniform packing in crystal structures and clumped arrangements in decoys, as observed previously 4 ; these hydrophobic atoms prefer a small amount of void volume immediately surrounding the atom and discourage void volume further from the atomic surface. This effect is observed for all atom types but is most pronounced for hydrophobic atoms.…”
supporting
confidence: 81%
“…However, the total cavity volume is not a good discriminator between computational predictions and corresponding X-ray structures (Supporting Information 2). The original version of RosettaHoles 4 showed that discrimination between computational models and crystal structures can be achieved using volumetric information. In this updated version, we seek to achieve better performance with a simplified method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each structure was subjected to relaxation under the Rosetta full-atom potential (21,22). Packing quality was analyzed using the RosettaHoles metric (16,17). A count of all buried, unsatisfied hydrogen bonds was obtained using a SASA probe of 1.4 Å. Hydrogen bonds were defined with a strict geometric criteria (23).…”
Section: Methodsmentioning
confidence: 99%
“…In the following, we present an automated protocol, Rosetta VIP (void identification and packing), for improving the packing of a structural model. We use the RosettaHoles analysis tool (16,17) and a simple geometric scoring function to identify a small set of mutations that may yield improved packing. We are able to devote more effort toward evaluating this reduced set of possibilities, including consideration of computationally expensive refinement steps incorporating backbone flexibility and off-rotamer side-chain freedom.…”
mentioning
confidence: 99%